2020
DOI: 10.3390/cancers12103043
|View full text |Cite
|
Sign up to set email alerts
|

The Role of GDF15 in Regulating the Canonical Pathways of the Tumor Microenvironment in Wild-Type p53 Ovarian Tumor and Its Response to Chemotherapy

Abstract: Background: The standard treatment of ovarian cancer is surgery followed by a chemotherapeutic combination consisting of a platinum agent, such as cisplatin and a taxane-like paclitaxel. We previously observed that patients with ovarian cancer wild-type for p53 had a poorer survival rate than did those with p53 mutations. Thus, a better understanding of the molecular changes of epithelial ovarian cancer cells with wild-type p53 in response to treatment with cisplatin could reveal novel mechanisms of chemoresis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Activation of the p53 was also demonstrated to be responsible for GDF15 expression [87]. Recent evidence showed that GDF15 modulates the canonical pathways in wild‐type p53 ovarian cancer cells and contributes to chemoresistance [88]. In the present study, we used the NUGC‐3 gastric cancer cells belonging to the p53‐mutant cell line [89].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the p53 was also demonstrated to be responsible for GDF15 expression [87]. Recent evidence showed that GDF15 modulates the canonical pathways in wild‐type p53 ovarian cancer cells and contributes to chemoresistance [88]. In the present study, we used the NUGC‐3 gastric cancer cells belonging to the p53‐mutant cell line [89].…”
Section: Discussionmentioning
confidence: 99%
“…At present, the main chemotherapeutic drugs for ovarian cancer are cisplatin, paclitaxel and so on 26 . However, due to the emergence of drug resistance in ovarian cancer, the therapeutic effect of cisplatin is less potent, and there is still the high mortality of ovarian cancer 27 .…”
Section: Discussionmentioning
confidence: 99%
“…RNA-seq was performed at the MD Anderson Cancer Center Advanced Technology Genomics Core Laboratory as previously described [ 22 , 30 ]. Total RNA from the same 14 frozen WGS samples was prepared using an RNeasy Mini Kit (Qiagen).…”
Section: Methodsmentioning
confidence: 99%